Development of Facial Area and Object Detection around The Eye Technique using Image Processing - Suksukont, Aekkarat; Sopasoap, Suppakitti; Srinonchat, Jakkree (Journal of Applied Research on Science and Technology (JARST), 2021)
Searching the facial area using image processing is an important step to design face recognition system. But, to detect the facial area is still problem for research in order to the shape and face feature are totally difference in each person. This research presents the development object detection technique in facial area and around eye on YCbCr with HSV color image. In the experiment, 200 images are used as the input which can be classified into two groups 1) 100 images without background pattern and 2) 100 images with background pattern. The YCbCr color model technique is then applied to all images to classify the skin color from the background. In the Cb, Cr of YCbCr and HSV color model technique provides the similar skin color of image index. The sobel edge detection technique is then used to detect the face feature. The image segmentation technique is finally used to search the object obstruction around the eye. The experiment results show that provides the accuracy as 97% and 92% for detect the face position and detect the object obstruction around the eye respectively, in the term of the image without background pattern. Also it provides the accuracy as 87% and 83% for detect the face position and detect the object obstruction around the eye respectively, in the term of the image with background pattern. Then the only YCbCr color image. The experiment of this research show that it can increase the performance of detect the object obstruction around the eye approximately 7% in the term of image without background pattern. Moreover, in the term of image with background pattern, it can increase the performance of detect the face position and detect the object obstruction around the eye approximately 9% and 5% respectively.